Array-CGH in pediatric neurology: A prospective observational study. (December 2016) - Vitaliti, Giovanna; Pavone, Piero; Motamed-Gorji, Nazgol; Matin, Nassim; Vecchio, Michele; Ledda, Caterina; Lubrano, Riccardo; Falsaperla, Raffaele
Array-comparative genomic hybridization (Array-CGH) has been proposed as the first efficient approach to scan the entire genome for variations in DNA copy number. This diagnostic method is based on the study of total genomic DNA isolated from any sample and reference cell populations, differentially labelled and hybridized to DNA microarrays. The method has been initially applied in clinical genetics research and has recently also been used in cancer research, as tumor genomes have a wide variety of copy number phenotypes, indicating different types of genetic instability. In this field, array-CGH has been demonstrated to be an efficient diagnostic method to provide information on the location of important cancer genes. Recently the use of array-CGH has been expanded, including the analysis of constitutional abnormalities, to diagnose subtending mutations of neurologic diseases, with promising results in diagnosing genetic mutations otherwise not evident with other genetic tests. We performed a prospective study on the efficiency of array-CGH in the genetic-molecular diagnosis of pediatric patients affected by developmental delay and mental retardation associated with clinical signs of dimorphism and/or other relevant neurological symptoms. In our study, we had a detection rate of 22.71% by array-CGH analysis and we were able to take more precise genetic information for microdeletion and microduplication of our cohort of patients with developmental delay and/or idiopathic mental retardation and/or dimorphic face and/or epilepsy. In our opinion, we think that these findings would be helpful in early diagnosis and family genetic counseling, above all in those clinical neurologic cases in which other diagnostic tests have not succeed in performing a diagnosis.